Text-fig. 7. a–d: Zelkova zelkovifolia. a: Fruiting twig, Oriolo MSF 639. b: Oriolo MSF 685. c: Oriolo MSF 859. d: Oriolo MSF 947. e: Unknown leaf fragment resembling Lonicera nigra L., 1753, Oriolo MSF 859. f: Crataegus aff. monogyna Oriolo MSF 639-1. g: Fagus aff. sylvatica Oriolo MSF 648. Scale bars 10 mm (a–g). in The Late Early Pleistocene Flora Of Oriolo, Faenza (Italy): Assembly Of The Modern Forest Biome - Denk, Thomas; Sami, Marco; Teodoridis, Vasilis; Martinetto, Edoardo (Zenodo, 2022)
Text-fig. 7. a–d: Zelkova zelkovifolia. a: Fruiting twig, Oriolo MSF 639. b: Oriolo MSF 685. c: Oriolo MSF 859. d: Oriolo MSF 947. e: Unknown leaf fragment resembling Lonicera nigra L., 1753, Oriolo MSF 859. f: Crataegus aff. monogyna Oriolo MSF 639-1. g: Fagus aff. sylvatica Oriolo MSF 648. Scale bars 10 mm (a–g). Published as part of Denk, Thomas, Sami, Marco, Teodoridis, Vasilis & Martinetto, Edoardo, 2022, The Late Early Pleistocene Flora Of Oriolo, Faenza (Italy): Assembly Of The Modern Forest Biome, pp. 217-262 in Fossil Imprint 78 (1) on page 231, DOI:10.37520/fi.2022.009, http://zenodo.org/record/7167867